Paediatric doctors adherence to GMC guidance on confidentiality. (29th September 2015) - Jones, C; Hull, R; Wheeler, R
Abstract : Aims: The General Medical Council (GMC) has recently published guidance on confidentiality, readily accessible to all registered doctors. Our audit aims to review current practice in line with the GMC guidance. Methods: Interviews of paediatric doctors were conducted regarding their current practice and maintenance of patient confidentiality. Question design was based upon "Confidentiality: Frequently Asked Questions (FAQs)" published by the GMC. The audit standard was the confidentiality guidance published in October 2009. Results: 40 doctors were interviewed (consultants (14), registrars (17) and SHO's (9)). Conclusion: Children's doctors' appear to be aware of the existence of guidance, but find its application impractical. The results demonstrate a lack of application of the GMC's guidance in some areas of the management of health records, despite this information being readily available. While the audit indicates that the "relaxed" practice of communicating patient information on the ward could lead to inadvertent disclosure, the reverse was true with the disclosure of patient information to Public Registers. This was poorly understood; the guidance is not being followed, and data flow to registers may be impeded. With research, teaching and child protection, where clear protocols exist, the guidance is better understood and followed. This disparity reflects the different levels of knowledge of confidentiality for specified areas of children's practice. Maintaining patient confidentiality is the cornerstone of any patient-doctor relationship, enabling patients to seek medical advice in trust, safety and it is their right by law. However, for effective patient care, advancements in research, education and public health, sharing of information is vital. Doctors require a clear understanding of confidentiality, which has not been demonstrated by our audit.